STАGES ОF DEVELОPMENT ОF THE INSURАNCE INDUSTRY IN UZBEKISTАN (Web of Technology: Multidimensional Research Journal, 2024)
This article provides proposals and recommendations related to the insurance services implemented in the national insurance market of Uzbekistan in recent years and their improvement.